2013
DOI: 10.1590/s1679-45082013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Características do estudo eletrofisiológico na Doença de Chagas

Abstract: Objective:Chagas disease has become a global problem due to changing migration patterns. An electrophysiological study is generally indicated for assessing sinus node function, conduction through the atrioventricular node and His-Purkinje system, in addition to evaluating the mechanisms of arrhythmia. The aim of this study was to describe the characteristics of electrophysiological study findings in patients with Chagas disease.Methods:A retrospective descriptive study of 115 consecutive patients with Chagas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…A literatura médica relacionada ao tratamento das arritmias e prevenção de morte súbita na CCDC é relativamente escassa e insuficiente para a formulação de recomendações fortes que se apoiem em evidências diretamente obtidas em estudos aleatorizados, indiscutivelmente comprovando eficácia terapêutica (nível A de evidência). 1 , 668 No entanto, a CCDC compartilha várias similaridades com diversas cardiopatias extensamente estudadas, em particular aquelas que cursam com fibrose miocárdica e disfunção sistólica (global ou segmentar), tais como a CMI e a CMD, 669 permitindo que o raciocínio terapêutico siga bases fisiopatológicas semelhantes. Dessa forma, o tratamento e a prevenção das arritmias ventriculares e supraventriculares na CCDC tendem a seguir, em linhas gerais, orientações semelhantes às das demais cardiopatias.…”
Section: Condutas Terapêuticas Nas Arritmias Cardíacasunclassified
See 2 more Smart Citations
“…A literatura médica relacionada ao tratamento das arritmias e prevenção de morte súbita na CCDC é relativamente escassa e insuficiente para a formulação de recomendações fortes que se apoiem em evidências diretamente obtidas em estudos aleatorizados, indiscutivelmente comprovando eficácia terapêutica (nível A de evidência). 1 , 668 No entanto, a CCDC compartilha várias similaridades com diversas cardiopatias extensamente estudadas, em particular aquelas que cursam com fibrose miocárdica e disfunção sistólica (global ou segmentar), tais como a CMI e a CMD, 669 permitindo que o raciocínio terapêutico siga bases fisiopatológicas semelhantes. Dessa forma, o tratamento e a prevenção das arritmias ventriculares e supraventriculares na CCDC tendem a seguir, em linhas gerais, orientações semelhantes às das demais cardiopatias.…”
Section: Condutas Terapêuticas Nas Arritmias Cardíacasunclassified
“…Medical literature related to arrhythmia treatment and sudden death prevention in CCCD is scarce and insufficient for the formulation of strong recommendations supported by evidence directly obtained from randomized studies and that indisputably proves therapeutic efficacy (level of evidence A). 1 , 668 However, CCCD shares similarities with several extensively studied cardiopathies, particularly those with myocardial fibrosis and systolic dysfunction (global or segmental), such as ICM and DCM, 669 allowing the therapeutic rationale to follow similar pathophysiological bases. Thus, the treatment and prevention of ventricular and supraventricular arrhythmias in CCCD tend to follow directions similar to those of the other cardiopathies.…”
Section: Therapeutic Management Of Cardiac Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation
“…I read with interest the article by Cedraz et al ( 1 ) describing their findings on the electrophysiological study of 115 chagasic patients. The authors reported that the presence of right bundle branch block (RBBB) was associated with less induction of sustained ventricular tachycardia or ventricular fibrillation (VT/VF) in a univariate analysis.…”
mentioning
confidence: 99%
“…Li com interesse o estudo de Cedraz et al, ( 1 ) que descreveram os achados do estudo eletrofisiológico de 115 chagásicos. Os autores demonstraram que a presença do bloqueio do ramo direito (BRD) esteve relacionada a menor indução de taquicardia ventricular sustentada ou fibrilação ventricular (TV/FV) pela análise univariada.…”
unclassified